Binding of the 5′-Triphosphate End of mRNA to the γ-Subunit of Translation Initiation Factor 2 of the Crenarchaeon Sulfolobus solfataricus. Issue 19 (25th September 2015) - Arkhipova, Valentina; Stolboushkina, Elena; Kravchenko, Olesya; Kljashtorny, Vladislav; Gabdulkhakov, Azat; Garber, Maria; Nikonov, Stanislav; Märtens, Birgit; Bläsi, Udo; Nikonov, Oleg
Abstract: The heterotrimeric archaeal IF2 orthologue of eukaryotic translation initiation factor 2 consists of the α-subunit, β-subunit and γ-subunit. Previous studies showed that the γ-subunit of aIF2, besides its central role in Met-tRNAi binding, has an additional function: it binds to the 5′-triphosphorylated end of mRNA and protects its 5′-part from degradation. Competition studies with nucleotides and mRNA, as well as structural and kinetic analyses of aIF2γ mutants, strongly implicate the canonical GTP/GDP-binding pocket in binding to the 5′-triphosphate end of mRNAs. The biological implication of these findings is being discussed. Graphical Abstract: Highlights: 5′-end GTP of mRNAs binds to the canonical nucleotide-binding pocket of SsoIF2γ.